Economic empowerment of the Chinese Muslim community in Malaysia: challenges, opportunities and prospects - Kassim, Salina; Fatah Yasin, Raudlotul Firdaus; Yap, Johari; Yap Yun Hin, Taufiq (IIUM Press, 2018)
According to the official figures, the number of people with Chinese descendants who are registered as Muslims in Malaysia (or the Chinese Muslims) stood at 42,048 persons in the year 2010 compared to 57,277 persons in the year 2000 (Department of Statistics, Malaysia, 2015; Abdullah and Shukri, 2008). Despite being small in numbers, the Chinese Muslims in Malaysia have continued to make increasing contribution socially and economically. In terms of economic profiling, majority of the Chinese Muslim community in Malaysia falls in the middle-income group (PERKIM, 2017). According to Ann Wan Seng (2011), the Chinese Muslim community in Malaysia has its own economic position. The Chinese Muslims make their presence mainly in the halal food industry with their well-known restaurant chains all over the country, also in the education field, entertainment industry, trading businesses, and dakwah efforts (Kassim et al., 2017)